(Invited) Silicon Nanostructures: A Versatile Material for Photonics. (29th July 2016) - Bisadi, Zahra; Cortelletti, Paolo; Zanzi, Andrea; Piotto, Chiara; Fontana, Giorgio; Bettotti, Paolo; Scarpa, Marina; Pavesi, Lorenzo
Abstract : Silicon is the most common semiconductor in technology. Its main limit is the lacking of efficient light emission properties. Here quantum effects are exploited to fabricate optically active silicon photonics elements. The manuscript reports recent results obtained in different research fields spanning from bio- to integrated-photonics and nonlinear optics.